POTENSI PENGEMBANGAN KOPERASI SYARI’AH DI PONDOK PESANTREN DAN MASJID DI KABUPATEN JEMBER - Hepni; Abd. Rokhim; Bambang (Al'Adalah, 2016)
Rasulullah SAW extremely motivates his follower to do business, since business is the way to get money speedily. It is proven by command for doing business in a good way and lawful. Syariah cooperation is a part of syariah economic system which has characteristic and values of the concept “amar ma’ruf nahi munkar” (order for doing good things and prevent for doing bad things) which means to do the right way and leave the bad way. Syariah economic is stressed on justice; teach the superior concept in facing mone- tary fluctuation compared to conventional system. Cooperation is joint enterprises engaged in the field of economy, which comprise of economically weak who join voluntarily generally and on the basis of rights equality and the obligation to make an effort which aims to fulfill their member’s need.